Imaging Tumor Cell Movement In Vivo. Issue 1 (1st March 2013) - Entenberg, David; Kedrin, Dmitriy; Wyckoff, Jeffrey; Sahai, Erik; Condeelis, John; Segall, Jeffrey E.
Abstract: This unit describes the methods that we have been developing for analyzing tumor cell motility in mouse and rat models of breast cancer metastasis. Rodents are commonly used both to provide a mammalian system for studying human tumor cells (as xenografts in immunocompromised mice) as well as for following the development of tumors from a specific tissue type in transgenic lines. The Basic Protocol in this unit describes the standard methods used for generation of mammary tumors and imaging them. Additional protocols for labeling macrophages, blood vessel imaging, and image analysis are also included. Curr. Protoc. Cell Biol . 58:19.7.1‐19.7.19. © 2013 by John Wiley & Sons, Inc.